Chemical Properties of Starch 2020
DOI: 10.5772/intechopen.90286
|View full text |Cite
|
Sign up to set email alerts
|

Micrometrics and Morphological Properties of Starch

Abstract: Starch occurs in form of granules and constitutes a primary manner in which of carbohydrates are stored chiefly in seeds and underground organs and sparingly in other morphological parts such as leaf and bark parts of plants. Grains of transitional starch can be found in the stroma of chloroplast and cytoplasm in leaf parts when exposed to the sun and transferred to organs for storage at dark times. The shape and size, ratio of amylose and amylopectin content of starch grains are peculiar to different biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Figure 1A shows that the morphology of D. sagittifolia free starch granules has cylindrical, rod-like or oblong and oval shapes that are symmetrical with smooth surfaces and with lengths between 134 and 179 m. Riley et al [21] reported similar shapes for certain cultivars of Dioscorea alata. Starches high in amylose are many times more elongated [40]. A value of 23.65% amylose obtained in this study is high enough to warrant the elongated shapes observed herein.…”
Section: 3: Morphological Propertiessupporting
confidence: 62%
See 1 more Smart Citation
“…Figure 1A shows that the morphology of D. sagittifolia free starch granules has cylindrical, rod-like or oblong and oval shapes that are symmetrical with smooth surfaces and with lengths between 134 and 179 m. Riley et al [21] reported similar shapes for certain cultivars of Dioscorea alata. Starches high in amylose are many times more elongated [40]. A value of 23.65% amylose obtained in this study is high enough to warrant the elongated shapes observed herein.…”
Section: 3: Morphological Propertiessupporting
confidence: 62%
“…Other factors capable of influencing the starch granule properties are temperature, storage and cultural practices [41]. Fatokun [40] reported that the sizes of granules of starch have been observed to range from small (2 10…”
Section: 3: Morphological Propertiesmentioning
confidence: 99%
“…1 Traditionally, this biopolymer has been used in the food industry, however, thanks to the advancement of technology and increasing research, starch is not limited only to the food industry anymore, and there are many other industries like textiles and paper, chemicals, agriculture, medicine, and engineering industries that benefit starch and its applications. 2…”
Section: A Little Bit About Starchmentioning
confidence: 99%
“…1 Despite the numerous natural sources of starch, about 80% of the global starch production comes from Zea mays (corn). 2…”
Section: A Little Bit About Starchmentioning
confidence: 99%
“…[6]. Likewise, starch, a natural polymer mostly found in plants, is present in a granular form [7]. Basically, plants genotype and cultural practice may differ in the morphology of starch granules which are mostly present in seeds, roots, tubers, stems and leaves [8].The starch-based bioplastic can serve as an alternative material for existing commodity plastics [9].…”
Section: Introductionmentioning
confidence: 99%